Environmental exposures associated with atopy in a rural community in Gwanda district, Zimbabwe: a cross-sectional study - Vuyelwa Ndlovu; Vuyelwa Ndlovu; Moses Chimbari; Pisirai Ndarukwa; Pisirai Ndarukwa; Elopy Sibanda; Elopy Sibanda (Frontiers in Public Health)
IntroductionThe increasing prevalence of allergic diseases in Zimbabwe may be attributed to changing environmental exposure patterns. In this study, we sought to identify the most influential environmental and lifestyle factors that may explain the observed atopy in a rural community in Zimbabwe.MethodsUsing a cross-sectional study, information on a wide array of environmental and lifestyle exposures was self-reported by a sample of participants (children aged <18 years and adults aged ≥18 years) in the Gwanda district, Zimbabwe. To consenting participants, we performed skin prick testing (SPT) at a local clinic in Gwanda district to identify atopic individuals. Variables with a p value <0.25 from univariate analysis were included in backward-elimination multiple logistic regression analysis. Separate regression analyses were conducted for children (n = 108), adults (n = 388), and a subgroup of adults who reported ever being employed in any potentially harmful occupation (n = 153).ResultsCompared with boys, girls were more likely to be sensitised to at least one allergen (OR = 4.87, 95% CI = 1.22–19.51). Among adults, the likelihood of sensitisation increased with increasing age (OR = 1.02, 95% CI = 1.01–1.03) and with a history of bloody urine and/or schistosomiasis (OR = 2.20, 95% CI = 0.98–4.95). In the subgroup of adults who reported ever being employed in any potentially harmful occupation, atopic sensitisation was associated with a history of tuberculosis (TB; OR = 3.37, 95% CI = 1.08–10.52) and a history of bloody urine and/or schistosomiasis (OR = 4.36, 95% CI = 1.40–13.65). Other notable, though not significant, factors were passive or parental smoking, alcohol consumption, indoor dampness and visible mould on walls.ConclusionGirls were more likely to be sensitised to at least one allergen when compared to boys. Among adults, atopic sensitisation was positively associated with age, parental smoking, alcohol consumption and history of bloody urine or schistosomiasis but negatively associated with indoor cooking. A history of TB or helminth infection increased the likelihood of atopy among adults with history of employment. Longitudinal studies to explore the temporal and causal relationships between these factors and allergic outcomes are essential. There is a need for early public health interventions to address environmental and lifestyle factors for the prevention and control of allergic diseases in African rural communities.